DETERMINATION OF FORCE LOAD ON THE UPPER PART OF ORTHOPEDIC AND POSTOPERATIVE SHOES - SHCHERBAN, VOLODYMYR; PONOMARENKO, TATIANA; SHCHERBAN, YURYJ (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The results of determining the force load on the upper part of orthopedic and postoperative shoes, taking into account the bending of the sole, are presented. To determine the force of the load on the top of the postoperative orthopedic shoes, the friction forces between the side surfaces of the shoes and the outer sides of the foot were neglected in the work. Thus, the task was reduced to the compilation of equilibrium equations of a plane system of forces. To determine the unknown forces, it was necessary to compile a system of two equilibrium equations, which will represent the algebraic sums of the projections of all forces on the horizontal and vertical axes, which will be equal to zero. The most common type of deformation acting on shoe parts during manufacturing and operation is stretching and bending. It is the last factor that affects the force load on the upper part of orthopedic and postoperative shoes. Deviation of the human musculoskeletal system from the normal anatomical structure and functioning is one of the serious and widespread ailments of the population. An important factor in reducing the inconvenience caused by this disease is the rational choice of orthopedic shoes. Compliance of orthopedic footwear with the functions that rely on it (supporting the arch of the foot, relieving painful areas, making the limb supportive, increasing the area of ​​foot support) is achieved by a reasoned approach to choosing the design of the product, including in the structure of special, special shape and size details, etc.. Degree compliance of this type of footwear with the real needs of the consumer depends on a complex of factors, and the ability to satisfy them is largely determined by the optimal ratio of indicators of reliability and comfort in the use of upper materials. Textile materials are widely used in the footwear industry for uppers, insoles, insoles, linings, and other parts of various types of footwear. This is caused by their valuable consumer properties, such as low hardness and surface density, pleasant texture, high heat-insulating properties, and a variety of artistic and colorful decoration.